Perioperative Neurocognitive Disorder: State of the Preclinical Science. (January 2020) - Eckenhoff, Roderic G.; Maze, Mervyn; Xie, Zhongcong; Culley, Deborah J.; Goodlin, Sarah J.; Zuo, Zhiyi; Wei, Huafeng; Whittington, Robert A.; Terrando, Niccolò; Orser, Beverley A.; Eckenhoff, Maryellen F.
Abstract : The purpose of this article is to provide a succinct summary of the different experimental approaches that have been used in preclinical postoperative cognitive dysfunction research, and an overview of the knowledge that has accrued. This is not intended to be a comprehensive review, but rather is intended to highlight how the many different approaches have contributed to our understanding of postoperative cognitive dysfunction, and to identify knowledge gaps to be filled by further research. The authors have organized this report by the level of experimental and systems complexity, starting with molecular and cellular approaches, then moving to intact invertebrates and vertebrate animal models. In addition, the authors' goal is to improve the quality and consistency of postoperative cognitive dysfunction and perioperative neurocognitive disorder research by promoting optimal study design, enhanced transparency, and "best practices" in experimental design and reporting to increase the likelihood of corroborating results. Thus, the authors conclude with general guidelines for designing, conducting and reporting perioperative neurocognitive disorder rodent research. Abstract : A bewildering variety of preclinical postoperative cognitive dysfunction studies has been reported over the last two decades. Herein the authors succinctly summarize the approaches and models, some of the accrued knowledge, and suggestions for future design and reporting.